PENGUATAN KEBIJAKAN PEMERINTAH DAERAH DAN IMPLEMENTASI OTONOMI PENDIDIKAN - Mashuri, Saefuddin (Hunafa: Jurnal Studia Islamika, 2009)
In line with regional authonomy, an authonomy in education through the concept of decentralisation has become a national agenda. In effect, this requires serious attention from the local government. In this era, local government, which has a strong political will to implement an authonomy in education, will be able to improve the quality of education independently. This, in turn, will support local development which is relevant with local needs and potentials. Otherwise, the local government, that is not concerned with this issue, will be reluctant in improving the quality of education. As a consequence, they are not able to support local development towards establishing well-educated society.Kata Kunci: Â Â  kebijakan daerah, Pemerintah Daerah, potensi daerah, otonomi pendidikan, desentralisasi pendidikan